Customer service management training 101 : quick and easy techniques that get great results - Evenson, Renee (New York : AMACOM, 2012)
This training manual offers readers an easy-to-implement approach for equipping their people with the skills they need to excel in this important role. This book addresses important customer service areas including: making a good first impression projecting a positive attitude developing trust, establishing rapport, and making customers feel valued confidently handling 'difficult' customers and situations interacting effectively face-to-face, and via telephone and e-mail.
Includes index.
oif 08/09/14
Loan
Keywords: Customer services - management; Executives; Time management; Leadership; Communication in management